1993
DOI: 10.1128/jvi.67.3.1482-1492.1993
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 UL46 and UL47 deletion mutants lack VP11 and VP12 or VP13 and VP14, respectively, and exhibit altered viral thymidine kinase expression

Abstract: The gene products of herpes simplex virus type 1 UL46 and UL47 enhance the efficiency of aTIF (VP16)-mediated a gene expression through an unknown mechanism of action. To further characterize the function of the UL46-and UL47-encoded proteins during virus infection, a series of isogenic herpes simplex virus type 1 strain F-derived UL46 and UL47 single-deletion mutants and a UL46/47 double-deletion mutant were constructed and compared with the wild type. Analysis of purified virions obtained from the UL46 delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 50 publications
(169 reference statements)
1
49
0
Order By: Relevance
“…This product seems not to be essential for growth of virus in cell culture. Recent calculations (268) indicate that there are close to 1300 molecules per virion, which is considerably more than previously estimated (86).…”
Section: Vp11/12mentioning
confidence: 74%
See 3 more Smart Citations
“…This product seems not to be essential for growth of virus in cell culture. Recent calculations (268) indicate that there are close to 1300 molecules per virion, which is considerably more than previously estimated (86).…”
Section: Vp11/12mentioning
confidence: 74%
“…Although the existence of two structural phosphoproteins designated VPll and VP12 with molecular weights of 93K and 87K, respectively, has been known for a long time (124, 232), information about them has been scarce until deletion mutants were recently made by Zhang & Mcfiight. These authors were thus able to show that both proteins are present in the tegument and are encoded by gene UL46 (268). It was suggested that VPll and VP12 were two differently phosphorylated forms of the same primary translation product.…”
Section: Vp11/12mentioning
confidence: 93%
See 2 more Smart Citations
“…This report demonstrates that the major tegument protein VP16 and the major DNA binding protein ICP8 of HSV-1 are immunogenic in humans, even though a T cell recall response with blood monocytes serving as antigen presenting cells could not be demonstrated in HSV-1 seropositive healthy individuals. This was surprising at first as both proteins are produced in large amounts during infection compared to other proteins [Zhang and McKnight, 1993] and have been shown to be essential for productive viral replication in vivo [Conley et al, 1981;Ace et al, 1989]. It seems likely that if infected cells acted as facultative antigen presenting cells this presentation obviously does not induce long-lasting T cell memory for these antigens.…”
Section: Discussionmentioning
confidence: 99%